Nepenthes megastoma (Nepenthaceae), a micro-endemic pitcher plant from Puerto Princesa Subterranean River National Park, Palawan, Philippines - Altomonte, John Charles A.; Collantes, John Paul R.; Mangussad, Vernaluz; Bustamante, Rene Alfred Anton; Robinson, Alastair S. (Phytotaxa, 2025)
Nepenthes megastoma is described and illustrated as a new species from the Puerto Princesa Subterranean River National Park, a UNESCO World Heritage Site in Palawan Philippines. This carnivorous tropical pitcher plant is currently known from just three locations in the Mount Saint Paul karst formation, where it grows on vertical limestone walls. Morphologically, N. megastoma is characterised by its highly branched stems, campanulate pitchers, peltate tendril exsertion, dimorphic upper pitchers, and unidirectionally upturned female flowers. It is assessed as Critically Endangered under the IUCN Red List criteria, based on its restriction to three subpopulations comprising few total individuals. Pitcher morphology suggests a degree of ecological-functional convergence with N. campanulata of Borneo, though overall morphology indicates a probable close affinity with the widespread Palawan endemic N. philippinensis.